Affective components in promoting physical activity: A randomized controlled trial of message framing - Carfora, Valentina; Biella, Marco; Catellani, Patrizia (Frontiers in psychology, 2022)
Although the study of the affective components involved in predicting physical activity is spreading faster and faster, there is a lack of studies testing their role when promoting physical activity through message interventions. In the present study, we considered these components by focusing on how anticipated affective reactions and emotional processing of the messages influence receivers’ affective attitude toward physical activity, concurrent behavior, and future intention. A sample of 250 participants was involved in an intervention relying on prefactual (i.e., “If … then…”) messages promoting physical activity. All messages were sent through a research app and were focused on the expected consequences of exercising (or not exercising). Four experimental conditions involving messages differing as to their outcome sensitivity framing (i.e., gain, non-loss, non-gain, and loss) were compared to a control condition. Results showed that reading gain and non-gain messages enhanced the positive affective attitude toward physical activity, compared to control. Enhanced affective attitude after the intervention increased, in turn, self-reported physical activity and future intention. Interestingly, gain messages were even more persuasive for people with a low level of positive anticipated affective reactions. Furthermore, their effectiveness was especially attributable to the elicitation of hope in receivers. Discussion focuses on the advantages of considering affective components and their implications when promoting physical activity.
Gesehen am 20.10.2022